Investigating volatile compounds in the Bacteroides secretome - Shagaleeva, Olga Yu; Kashatnikova, Daria A.; Kardonsky, Dmitry A.; Konanov, Dmitry N.; Efimov, Boris A.; Bagrov, Dmitry V.; Evtushenko, Evgeniy G.; Chaplin, Andrei V.; Silantiev, Artemiy S.; Filatova, Julia V.; Kolesnikova, Irina V.; Vanyushkina, Anna A.; et al. (Frontiers in Microbiology, 2023)
Microorganisms and their hosts communicate with each other by secreting numerous components. This cross-kingdom cell-to-cell signaling involves proteins and small molecules, such as metabolites. These compounds can be secreted across the membrane via numerous transporters and may also be packaged in outer membrane vesicles (OMVs). Among the secreted components, volatile compounds (VOCs) are of particular interest, including butyrate and propionate, which have proven effects on intestinal, immune, and stem cells. Besides short fatty acids, other groups of volatile compounds can be either freely secreted or contained in OMVs. As vesicles might extend their activity far beyond the gastrointestinal tract, study of their cargo, including VOCs, is even more pertinent. This paper is devoted to the VOCs secretome of the Bacteroides genus. Although these bacteria are highly presented in the intestinal microbiota and are known to influence human physiology, their volatile secretome has been studied relatively poorly. The 16 most well-represented Bacteroides species were cultivated; their OMVs were isolated and characterized by NTA and TEM to determine particle morphology and their concentration. For a number of species, OMVs have been isolated and characterized here for the first time. In order to analyze the VOCs secretome, we propose a headspace extraction with GC-MS analysis as a new tool for sample preparation and analysis of volatile compounds in culture media and isolated bacterial OMVs. A wide range of released VOCs, both previously characterized and newly described, have been revealed in media after cultivation. We identified more than 60 components of the volatile metabolome in bacterial media, including fatty acids, amino acids and phenol derivatives, aldehydes and other components. We found active butyrate and indol producers among the analyzed Bacteroides species. Volatile compounds of bacterial OMVs were analyzed for the first time. We observed a completely different distribution of VOC in vesicles compared to the bacterial media for all analyzed Bacteroides species, including almost complete absence of fatty acids in vesicles. This article provides a comprehensive analysis of the VOCs secreted by Bacteroides species and explores new perspectives in the study of bacterial secretomes in relation the intercellular communication.